2006
DOI: 10.1080/10799890600932220
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for Protons or Lipid Messengers or Both?

Abstract: The subfamily of G protein-coupled receptors comprising GPR4, OGR1, TDAG8, and G2A was originally characterized as a group of proteins mediating biological responses to the lipid messengers sphingosylphosphorylcholine (SPC), lysophosphatidylcholine (LPC), and psychosine. We challenged this view by reporting that OGR1 and GPR4 sense acidic pH and that this process is not affected by concentrations of SPC or LPC previously reported as agonistic. The original publications describing GPR4, OGR1, and G2A as recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
90
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 36 publications
0
90
0
Order By: Relevance
“…18 Cultured collecting duct cells that express GPR4 mRNA endogenously exhibit peak GPR4 activity at pH 7.0, similar to findings in cells transfected with GPR4. 8,9,14,29 The dynamic range of (pH) responsiveness of GPR4 is consistent with a potential physiologic role for the receptor in the kidney interstitium. Although low pH of the kidney interstitium has been well appreciated, 30 -32 a new technique allowed Andreev et al 33 to demonstrate directly that fluctuations in interstitial pH were evident during changes in acid load.…”
Section: Discussionmentioning
confidence: 74%
“…18 Cultured collecting duct cells that express GPR4 mRNA endogenously exhibit peak GPR4 activity at pH 7.0, similar to findings in cells transfected with GPR4. 8,9,14,29 The dynamic range of (pH) responsiveness of GPR4 is consistent with a potential physiologic role for the receptor in the kidney interstitium. Although low pH of the kidney interstitium has been well appreciated, 30 -32 a new technique allowed Andreev et al 33 to demonstrate directly that fluctuations in interstitial pH were evident during changes in acid load.…”
Section: Discussionmentioning
confidence: 74%
“…8 Interpreting these studies is complicated, however, by the chemical reactions interlinking the CO 2 /HCO À 3 buffer components. Because the chemical interconversion between H þ , HCO À 3 , and CO 2 has not always been appreciated 6 and because consequences of altering pH, pCO 2 and [HCO A number of candidate molecules involved in acidbase sensing have been suggested, including G-protein coupled receptors (OGR1, GPR4, TDAG8) 9 and ion channels (ASICs) 10 sensitive to pH o . The activities of several intracellular enzymes (soluble adenylyl cyclase, 11 rho-kinase 12 and NO-synthase 12,13 ) also depend on [HCO À 3 ] or pH.…”
Section: Introductionmentioning
confidence: 99%
“…Along with others, we have recently found that OGR1 family receptors, including OGR1, GPR4, G2A, and TDAG8, which have previously been proposed as receptors for lysolipids, sense extracellular protons, most likely through histidine residues located on the extracellular region of the receptors, resulting in the modification of a variety of cell functions in association with the G protein-mediated stimulation of intracellular signaling pathways (31,32,43,47,48). It should be noted, however, that while the human G2A receptor elicits signaling responses to extracellular acidification similarly to human OGR1, GPR4, and TRDAG8 receptors when overexpressed in cell lines (35), in contrast to the murine OGR1, GPR4, and TDAG8 receptors, the murine G2A receptor is lacking in the histidine residue, which is postulated to sense extracellular proton, and insensitive to extracellular acidification (39).…”
mentioning
confidence: 99%